2021
DOI: 10.1186/s40792-021-01325-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and endoscopic cooperative surgery for advanced gastric cancer as palliative surgery in elderly patients: a case report

Abstract: Background The number of elderly patients with gastric cancer is increasing, with the very elderly often refusing radical gastrectomy with lymph node dissection. Such a patient presented to us and we proposed a palliative surgery involving gastric local resection using laparoscopy endoscopy cooperative surgery (LECS). Case presentation An 89-year-old woman presented to our hospital with progressing anemia. She had an aortic arch replacement for aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Although distal gastrectomy with lymph node dissection was the most adequate treatment, we performed LLR for local recurrence due to the patient's comorbidities. Recently, there have been an increasing number of case reports of local resection for gastric cancer in high-risk perioperative patients due to old age or comorbidities [1] , [2] , [10] . The extent of gastric resection and lymph node dissection is limited, resulting in less morbidity and early recovery compared with distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although distal gastrectomy with lymph node dissection was the most adequate treatment, we performed LLR for local recurrence due to the patient's comorbidities. Recently, there have been an increasing number of case reports of local resection for gastric cancer in high-risk perioperative patients due to old age or comorbidities [1] , [2] , [10] . The extent of gastric resection and lymph node dissection is limited, resulting in less morbidity and early recovery compared with distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, elderly people and patients with severe comorbidities have a high-risk of mortality and complication; consequently, a less invasive surgery, and not a typical gastrectomy, may be beneficial for them. Some studies have reported partial gastrectomy using laparoscopic and endoscopic cooperative surgery (LECS) as a palliative treatment for gastric cancer [1] , [2] , [3] . Here, we report our experience and tips for laparoscopic local resection (LLR), without the need for endoscopic submucosal dissection (ESD), for treating gastric cancer in a patient with severe comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the current indication for LECS is gastrointestinal stromal cell tumors (GIST) with a size of 2-5 cm. LECS has also been described in two case reports as palliative treatment for patients with AGC without being in a state to undergo gastrectomy (12)(13). To the best of our knowledge, no prospective trial has studied LECS for this indication.…”
Section: Trial Registrationmentioning
confidence: 99%
“…LECS was recently performed in an elderly patient who refused radical surgery as a palliative treatment[ 14 ].…”
Section: To the Editormentioning
confidence: 99%